108k views
4 votes
Note: Enter your answer and show all the steps that you use to solve this problem in the space provided. Solve the equation or formula for the indicated variable. T= 2 r π h + 2 π r ^2; for h

1 Answer

2 votes

For this case we have the following equation:


T = 2 \pi * r * h + 2 \pi * r ^ 2

We must solve the equation for the variable "h":

We subtract
2 \pi * r ^ 2 from both sides of the equation:


T-2 \pi * r ^ 2 = 2 \pi * r * h

We divide by
2 \pi * r on both sides of the equation:


\frac {T-2 \pi * r ^ 2} {2 \pi * r} = h\\h = \frac {T} {2 \pi * r} - \frac {2 \pi * r ^ 2} {2 \pi * r}\\h = \frac {T} {2 \pi * r} -r

Answer:


h = \frac {T} {2 \pi * r} -r

User Kevin Burdett
by
4.9k points